2007
DOI: 10.1002/rsa.20191
|View full text |Cite
|
Sign up to set email alerts
|

Random partitions with restricted part sizes

Abstract: ABSTRACT:For a subset S of positive integers let (n, S) be the set of partitions of n into summands that are elements of S. For every λ ∈ (n, S), let M n (λ) be the number of parts, with multiplicity, that λ has. Put a uniform probability distribution on (n, S), and regard M n as a random variable. In this paper the limiting density of the (suitably normalized) random variable M n is determined for sets that are sufficiently regular. In particular, our results cover the case S = {Q(k) : k ≥ 1}, where Q(x) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…The distribution of the number of parts in such partitions has been studied recently in [11] under some assumptions on growth of B k . Namely its is shown that if B k − ck β , β ∈ (0, 1), satisfies some additional condition then the number of parts in a random partition of n behaves like a nondegenerate random variable (explicitly specified in [11]) multiplied by n 1/(1+β) .…”
Section: Partitions With Restricted Part Sizesmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of the number of parts in such partitions has been studied recently in [11] under some assumptions on growth of B k . Namely its is shown that if B k − ck β , β ∈ (0, 1), satisfies some additional condition then the number of parts in a random partition of n behaves like a nondegenerate random variable (explicitly specified in [11]) multiplied by n 1/(1+β) .…”
Section: Partitions With Restricted Part Sizesmentioning
confidence: 99%
“…The distribution of the number of parts in such partitions has been studied recently in [11] under some assumptions on growth of B k . Namely its is shown that if B k − ck β , β ∈ (0, 1), satisfies some additional condition then the number of parts in a random partition of n behaves like a nondegenerate random variable (explicitly specified in [11]) multiplied by n 1/(1+β) . Theorem 6 shows that if just summands greater than tn 1/(β+1) , t > 0 are counted then their number is much less: it is proportional to n β/(1+β) and the coefficient converges in probability to a constant (depending on t).…”
Section: Partitions With Restricted Part Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak form of the limit shape in Theorem 3.3 is easily calculated via the statistical models in Khinchin [35], and more explicitly by Kerov and Vershik [56] -the same ones utilized by Fristedt [24] and Pittel [45]. The limit shape then follows by concentration and a local central limit theorem, or equivalently, asymptotic enumeration, via the inequality in equation (10.6); see also [27,12].…”
Section: Connections With Enumerative Combinatoricsmentioning
confidence: 99%
“…Specifically, we prove Proposition 1. Assume |Q| ≤ q, |M| ≤ 1, and let R be given by (1). Then, for sufficiently large x…”
Section: Bounds On the Tailsmentioning
confidence: 99%